(untitled) (GEOMATE Journal, 2017)
Physical modelling through full-scale and small-scale models is widely implemented in order to define specific aspects of the prototype behaviour. On the other hand, numerical modeling is essentially required to cope with the complex geotechnical problems due to the ability of considering and analyzing all aspects of the model and can afford more perception about the behavior of structures such as geosynthetic-reinforced embankments. In this study, four different cases of unreinforced and reinforced embankment models constructed on soft and stiff grounds were studied. Small-scale physical modelling by means of centrifuge tests and numerical modelling by means of finite element simulations were performed. As the small-scale model was rotated in different acceleration fields during the centrifuge test, the dimensions of the centrifugal model were different from the original state of the prototype in different stages of the test. This paper focused on developing a finite element simulation based on the dimensions of a centrifugal model in different incremental acceleration fields applied during the stages of the test. Comparing the results of finite element simulations with the measurements of the centrifuge tests showed a good agreement between the two methods, which verified the reasonableness of the finite element models in analysis of embankments based on small-scale centrifugal dimensions. Moreover, the results showed the different deformation behaviour for embankments on soft and stiff grounds and indicated the significant effect of the geosyntheic reinforcement on increasing the stability of the embankment on soft ground.